2020
DOI: 10.1021/acsenergylett.0c01901
|View full text |Cite
|
Sign up to set email alerts
|

Methoxy-Functionalized Triarylamine-Based Hole-Transporting Polymers for Highly Efficient and Stable Perovskite Solar Cells

Abstract: The hole-transporting layer is an essential component in a perovskite solar cell (PSC) and plays a key role in controlling both power conversion efficiency (PCE) and stability. Here, we report a new hole-transporting material (HTM), methoxy groupcontaining poly(triarylamine) (PTAA) (CH 3 O-PTAA), for efficient PSCs with improved thermal stability. As compared to commonly used PTAA (CH 3 -PTAA), CH 3 O-PTAA exhibits enhanced doping ability and stability under thermal stress. With CH 3 O-PTAA, (FAPbI 3 ) 0.85 (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
100
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(101 citation statements)
references
References 69 publications
0
100
0
Order By: Relevance
“…To further understand the effect of mixed compositions on the total solubility of the perovskite, we also measured the solubility of one of the best compositions for perovskite solar cells (MAPbBr 3 ) 0.15 (FAPbI 3 ) 0.85 at 30 • C and 90 • C [22,25]. In practice, mixed DMSO-DMF solvent is commonly used; therefore, we also tested the solubility of (MAPbBr 3 ) 0.15 (FAPbI 3 ) 0.85 in the mixture of DMF and DMSO (4:1 v/v).…”
Section: Resultsmentioning
confidence: 99%
“…To further understand the effect of mixed compositions on the total solubility of the perovskite, we also measured the solubility of one of the best compositions for perovskite solar cells (MAPbBr 3 ) 0.15 (FAPbI 3 ) 0.85 at 30 • C and 90 • C [22,25]. In practice, mixed DMSO-DMF solvent is commonly used; therefore, we also tested the solubility of (MAPbBr 3 ) 0.15 (FAPbI 3 ) 0.85 in the mixture of DMF and DMSO (4:1 v/v).…”
Section: Resultsmentioning
confidence: 99%
“…The PSCs with a n‐i‐p structure with organic hole transport materials (HTM) are vulnerable to heat despite offering a higher PCE than the PSCs with a p‐i‐n structure, and researchers have thus sought to discover thermally stable HTMs. A few polymeric HTMs such as poly(triaryl amine) (PTAA), [ 7 ] molecular HTMs such as metal phthalocyanines, [ 8 ] and an inorganic HTM, cuprous thiocyanate, [ 9 ] have shown long‐term stability at 85 °C with PCE exceeding 20%. We have reported that PSCs with application of copper phthalocyanine (CuPc) showed outstanding thermal stability up to 110 °C and temperature cycles.…”
Section: Introductionmentioning
confidence: 99%
“…In high-efficiency n-i-p typed PSCs, spiro-OMeTAD and p-TAA (Figure 1) are so far the most commonly used smallmolecule and polymeric hole transport materials (HTMs) for PSCs, respectively. [4][5][6][7]18,19] Actually, even a thin film of neat spiro-OMeTAD or p-TAA with a thickness of only a few tens of nanometers owns a considerable resistance, [18,20,21] which cannot meet the requirement of low internal resistance in high-efficiency PSCs. Several reports have shown that thin films of doped spiro-OMeTAD with improved electrical conductivity [22,23] can be used to prepare high-efficiency PSCs, but the resultant devices encounter severe PCE degradations at 85 °C.…”
mentioning
confidence: 99%
“…[24,25] In contrast, although the film-forming property of p-TAA is better, the PCEs of PSCs fabricated with thin films of doped p-TAA are always reduced due to lower conductivity, and the device thermostability at 85 °C is still far from ideal. [18] Apart from p-TAA, regioregular poly(3hexylthiophene) (P3HT, Figure 1) has also been tested as HTL of PSCs. [26,27] With respect to p-TAA, P3HT has a larger driving force for hole extraction and a higher hole mobility, but its charge recombination with perovskite is faster probably owing to the excessive interface interaction, [28] thereby it is hard to be used for high-efficiency PSCs if a delicate interfacial layer is not well inserted.…”
mentioning
confidence: 99%